Maxillary reconstruction with scapular tip chimeric free flap. Issue 3 (14th January 2021) - Ferri, Andrea; Perlangeli, Giuseppe; Bianchi, Bernardo; Zito, Francesca; Sesenna, Enrico; Ferrari, Silvano
Abstract: Purpose: Purpose of the article is to discuss the use of the scapular tip free flap (STFF) for the reconstruction of maxillary defects. Methods: A retrospective evaluation of patients who underwent maxillary reconstruction with STFF is presented. Patients were evaluated with respect to complications, function, and cosmesis. Results: Study population consisted of 53 patients. All flaps survived and partial bone resorption only occurred in a young patient. Minor complications included two instances of partial muscular necrosis. The donor site was primarily closed in all patients. Mouth opening was assessed as good (>3 cm) in 41 patients, partially limited (2–3 cm) in 9 patients, and limited (<2 cm) in 3 patients. Dental rehabilitation was achieved in 35 patients; esthetic results were assessed by patient as excellent in 19 patients, good in 28 patients, and poor in 6 patients. Conclusions: The scapular tip chimeric free flap represents an indispensable tool for reconstructive head and neck microsurgery. The main advantages of this technique are very low donor site morbidity and a long pedicle, as well as the potential for harvesting multiple flaps in a chimeric design; STFF represents the first choice for treatment of small postero‐lateral defects of the maxilla, and of wide and complex through‐and‐through defects involving all components of the midface.